Pengaruh Promosi Digital Dan Online Review Terhadap Brand Image Melawa Cafe KBC Batam - Fitrah Haryanto; Tirta Mulyadi; Eryd Saputra; Agung Arif Gunawan (Journal of Innovative and Creativity, 2025)
This study aims to determine the effect of digital promotion and online reviews on the brand image of Melawa Café Batam. The background of this research is based on the increasing use of social media as a marketing strategy for local culinary products. This research uses a quantitative method with an associative explanatory approach. Data were collected through questionnaires distributed to Melawa Café consumers who have visited, live in Batam City, and have social media accounts such as Instagram or TikTok. The sample consisted of 286 respondents selected using the purposive sampling technique. Data were analyzed using multiple linear regression with the help of SPSS software. The results show that digital promotion has a negative and significant effect on brand image, while online reviews have a positive and significant effect. Simultaneously, both variables have no significant effect on brand image. These findings indicate that managing customer reviews plays a greater role in building brand image than digital promotion activities. This research contributes to helping business owners design more effective digital marketing strategies to improve brand image in the social media era.